Unintentional home injuries among children aged 1–9 years in slums of Burdwan Municipality, West Bengal: A cross-sectional study - Mukherjee, Tanmoy; Roy, Sima; Mandal, Sutapa; Das, Dilip Kumar (Indian Journal of Child Health, 2018)
Context: Unintentional home injuries result in morbidities among children. Aims: This study aimed to find out the prevalence and patterns of unintentional home injuries among children aged 1–9 years, in slums of Burdwan Municipality; to determine an association of various sociodemographic factors with such injuries; and to assess known risk factors for unintentional injuries. Settings and Design: This community-based cross-sectional study was conducted in three randomly selected slums of Burdwan Municipality, West Bengal. Materials and Methods: The study was conducted during July–November 2017 among 219 children aged 1–9 years residing in the study area. Data were collected at the household level by interviewing the respondents, record review, and observation. The occurrence of any unintentional home injury during the last 1 year was considered to estimate period prevalence. Results: Overall prevalence of unintentional home injury was 19.6%; with 20.8% and 18.6% among girls and boys, respectively. Mean episode of injuries was 0.37±0.9 in a year. Majority of injury episodes were cut by fall (73.2%), affected ankle and foot (44%), and occurred in the living room (84.1%) and while playing (98.8%). Overcrowding (82.2%), access to sharps in the kitchen (59.4%), and sharp objects within reach in living rooms (44.7%) were the prevalent known risk factors at the households. Conclusions: Unintentional home injuries among children are substantially high in the area with some of theprevalent risk factors. Intensive health education activities for mothers and awareness campaigns for preventive measures need to be implemented.Context: Unintentional home injuries result in morbidities among children. Aims: This study aimed to find out the prevalence and patterns of unintentional home injuries among children aged 1–9 years, in slums of Burdwan Municipality; to determine an association of various sociodemographic factors with such injuries; and to assess known risk factors for unintentional injuries.Settings and Design: This community-based cross-sectional study was conducted in three randomly selected slums of Burdwan Municipality, West Bengal. Materials and Methods: The study was conducted during July–November 2017 among 219 children aged 1–9 years residing in the study area. Data were collected at the household level by interviewing the respondents, record review, and observation. The occurrence of any unintentional home injury during the last 1 year was considered to estimate period prevalence. Results: Overall prevalence of unintentional home injury was 19.6%; with 20.8% and 18.6% among girls and boys, respectively. Mean episode of injuries was 0.37±0.9 in a year. Majority of injury episodes were cut by fall (73.2%), affected ankle and foot (44%), and occurred in the living room (84.1%) and while playing (98.8%). Overcrowding (82.2%), access to sharps in the kitchen (59.4%), and sharp objects within reach in living rooms (44.7%) were the prevalent known risk factors at the households. Conclusions: Unintentional home injuries among children are substantially high in the area with some of the prevalent risk factors. Intensive health education activities for mothers and awareness campaigns for preventive measures need to be implemented.